Prosedur Pembedahan pada Hiperhidrosis Aksilaris dengan Teknik Tumesen Liposuction-Curettage - Danu Yuliarto; Wibisono Nugraha; Moerbono Mochtar; Ammarilis Murastami (MEDICINUS, 2022)
Hyperhidrosis is an excessive sweat production due to autonomic nerve dysfunction that occurs in areas with higher concentration of eccrine gland such as palms, soles of the feet, and axilla. Management of hyperhidrosis includes pharmacological and nonpharmacological approach. Patients with severe focal hyperhidrosis should consider surgical treatment or botulinum toxin injection. Tumescent liposuction with curettage is one of surgical technique option for the treatment of axillary hyperhidrosis. Case: A 32-year-old woman with complaint of excessive sweating, especially in the axillary area. The patient had received oral therapy from a dermatologist prior, but there was no improvement, so the patient was advised to undergo a surgical procedure. In this patient the tumescent liposuction-curettage procedure was performed. Discussion: Treatment of hyperhidrosis with both topical and systemic agents generally provides only temporary suppression of hyperhidrosis. In severe, disturbing cases, the treatment of choice for axillary hyperhidrosis is the surgical procedure. Combination of liposuction-curettage surgical method using tumescent anesthesia is relatively simple and safe. Reduction of apocrine gland secretion after liposuction-curettage takes a relatively long time. This surgical technique has many advantages, such as relatively minimal injury dan short recovery period. Follow-up after this combined liposuction-curettage procedure should be performed subjectively and objectively at 3, 6, and 12 months postoperative.